Evaluation of an Association of Blood Homocysteine Levels With Gastric Cancer Risk From 27 Case–Control Studies. Issue 20 (May 2016) - Xu, Wei; Cheng, Yuelei; Zhu, Huirong
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: High blood homocysteine levels may risk gastric cancer. However, observational studies have been plagued by chance, bias, confounding, or reverse causality. In this study, we assessed the relationship between blood homocysteine levels and gastric cancer by using a Mendelian randomization method, which is independent of nongenetic confounding. We took 2 steps to perform Mendelian randomization analysis. First, we evaluated the methylenetetrahydrofolate reductase (MTHFR) C677T association with gastric cancer by a meta-analysis of case-control studies including 7566 patients with gastric cancer and 10 640 control subjects from 27 Case–Control studies. Second, MTHFR C677T polymorphism, which affects the blood homocysteine levels, was used as an instrumental variable to calculate the risk and estimate the association of gastric cancer with this single nucleotide polymorphism (SNP). We obtained an estimate to the association of blood total homocysteine levels with this SNP from a meta-analysis of Genome-Wide Association Studies (GWAS), which comprises a total of 44 147 individuals. In our Mendelian randomization analysis, we demonstrated a significant effect of the blood homocysteine levels on gastric cancer risk, representing an OR of 2.56 (95% CI = 2.41–2.72; P  = 5.0×10 −4 ) for gastric cancer per 1-SD increase in the natural log-transformed blood total homocysteine levels. We proved that there is a causal relationship between blood total homocysteine and risk of gastric cancer, and this study will add insight into the treatment and pathology research of gastric cancer.